Penyuluhan Batas Usia Perkawinan Berdasarkan UU No. 16 Tahun 2019 dalam Upaya Pencegahan Stunting - Rahmanda Yudhatama Haglin; Fariska Jihan Setiyowati; Candra Adi Nugroho; Galih Agus Shoim; Ahmad Mukhlisin (Muria Jurnal Layanan Masyarakat, 2026)
Early marriage remains a serious issue in Indonesia, even though Law No. 16 of 2019 has established a minimum age of 19 years. This phenomenon is also identified within the environment of MA NU Miftahul Falah Cendono, Kudus, where strong social influences still trigger the practice of underage marriage among adolescents. Through counseling on the maturation of marriage age and socialization of blood-added tablet consumption, this program aims to increase students' understanding regarding the urgency of stunting prevention from legal and health perspectives. The implementation method uses normative and empirical juridical approaches through interactive discussions and evaluation of understanding. The results of the activity show a significant increase in the legal awareness and reproductive health of the students, thus the program is considered effective in building critical awareness in adolescents as agents of change in reducing the rates of early marriage and stunting